The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1080/08946566.2016.1168333
|View full text |Cite
|
Sign up to set email alerts
|

The Lichtenberg Financial Decision Screening Scale (LFDSS): A new tool for assessing financial decision making and preventing financial exploitation

Abstract: One of the challenges in preventing the financial exploitation of older adults is that neither criminal justice nor noncriminal justice professionals are equipped to detect capacity deficits. Because decision-making capacity is a cornerstone assessment in cases of financial exploitation, effective instruments for measuring this capacity are essential. We introduce a new screening scale for financial decision making that can be administered to older adults. To explore the scale’s implementation and assess const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Interrater reliability for overall ratings on the scale were presented in Lichtenberg et al; at that time, the complete rating scale contained 77 items. After preliminary analyses (Lichtenberg et al, 2016), the scale was shortened to 68 items (56 items for all participants and 12 additional items with skip patterns).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interrater reliability for overall ratings on the scale were presented in Lichtenberg et al; at that time, the complete rating scale contained 77 items. After preliminary analyses (Lichtenberg et al, 2016), the scale was shortened to 68 items (56 items for all participants and 12 additional items with skip patterns).…”
Section: Methodsmentioning
confidence: 99%
“…Declines in cognitive abilities and decision-making are linked to increased risk of financial exploitation. Boyle et al (2012) found that reduced decision-making is related to increased susceptibility to scams, and Lichtenberg et al (2016) assert that impaired decision-making abilities differentiate those who have in fact been victims of financial exploitation from those who have not.…”
Section: Literature Reviewmentioning
confidence: 99%
“…legal, financial, medical, mental health services) are in a position to prevent financial exploitation and would benefit from access to new instruments. The Lichtenberg Financial Decision Screening Scale (LFDSS) was introduced in 2016, along with evidence for its convergent validity (Lichtenberg et al, 2016). Using a sample of 213 participants, this study investigated the internal consistency of the LFDSS and its criterion validity based on ratings by professionals using the scale.…”
mentioning
confidence: 99%
“…Lichtenberg and colleagues (2016) recently introduced a new tool for assessing financial decision making, the Lichtenberg Financial Decision Screening Scale (LFDSS), and presented data that underscores the importance of measuring decision-making skills for both financial decision-making capacity and susceptibility to financial exploitation. Specifically, after administering the scale, ratings of financial transactional capacity for specific decisions by attorneys and financial services professionals were compared to ratings of a different sample by adult protective services (APS) professionals for cases in which financial exploitation was substantiated.…”
mentioning
confidence: 99%
See 1 more Smart Citation